Desigualdade, Interseccionalidade e políticas públicas: um estudo das narrativas da mídia sobre a epidemia de Zika vírus de maio de 2015 a maio de 2017. - BRAGA, Ivana Márcia Moraes (2019)
The media occupies a central place in the contemporary world with impacts on several areas of knowledge and life. In this work, we focus on analyzing the media narratives about the Zika virus epidemic in the newspapers O Estado de Maranhão and Folha de São Paulo, from May 2015 to May 2017. Our approach considers social contradictions, the historicity of subjects and social struggles, the socioeconomic and cultural conditions of the discourse production in order to construct an analysis that has as assumptions the multiple determinations of reality. We develop the research from a historical perspective and considering the social contradictions to point out the processes of social exclusion, exploitation and domination of the black population, seeking to articulate social, racial and gender inequality in the health-disease process. We also highlight the feminist production of knowledge about gender relations and denaturalization of female inferiority, in addition to explaining advances and tensions between theoretical perspectives. In this context, we present the intersectionality theory as a theoretical-methodological reference with more possibilities of making approximations to the life experience of black women. We also investigate the influence of the media as a subject of the public policy process and its relationship with the political and economic field, as well as characterize its participation in the Public Policy Cycle typology and the Multiple Streams model. We are also concerned with demonstrating the interrelationship among the media agenda-setting, the public agenda-setting, and the policy agenda-setting. We analyzed the main themes that compose the narrative of the Zika virus epidemic, considering how the categories gender, race and social class would emerge in these discourses, as well as others that appeared in association as patriarchy and woman. Based on this study, we observed that the media narratives on the Zika virus epidemic mostly focused on coverage of government actions, focusing on activities to combat the Aedes mosquito and contributed to naturalize inequalities and illness, strengthening the gender stereotypes, the invisibilization and silencing of black women as the most affected, as well as highlighting the close relationship between the media and governmental agenda that favors the maintenance of the social order based on racism, sexism, patriarchy and naturalization of poverty, harming the formulation of more assertive public policies, and that incorporate the demands of subalternized subjects.